2020
DOI: 10.1101/2020.04.13.039263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparativein vitrotranscriptomic analyses of COVID-19 candidate therapy hydroxychloroquine suggest limited immunomodulatory evidence of SARS-CoV-2 host response genes

Abstract: Hydroxychloroquine (HCQ) has emerged as a potential and controversial antiviral candidate therapy for COVID-19. While many clinical trials are underway to test the efficacy of HCQ as a treatment for COVID-19, underlying mechanisms of HCQ in the setting of COVID-19 remain unclear. Hence, we examined differential gene expression signatures of HCQ exposure, in vitro SARS-CoV-2 infection, and host signatures of COVID-19 in blood, bronchoalveolar lavage, and postmortem lung to evaluate whether HCQ transcriptome sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The top-ranked features (genes/transcripts) and rules were identified by applying these optimal machine learning models. According to recent publications [44][45][46][47][48][49][50][51], several identified top-ranked features and rule-involved features have been confirmed to be associated with the infection of a specific kind of pathogen, thus validating the efficacy and accuracy of the prediction in the current work. The detailed discussion can be found below.…”
Section: Discussionsupporting
confidence: 62%
“…The top-ranked features (genes/transcripts) and rules were identified by applying these optimal machine learning models. According to recent publications [44][45][46][47][48][49][50][51], several identified top-ranked features and rule-involved features have been confirmed to be associated with the infection of a specific kind of pathogen, thus validating the efficacy and accuracy of the prediction in the current work. The detailed discussion can be found below.…”
Section: Discussionsupporting
confidence: 62%
“…SARS-CoV-2 can also directly infect endothelial cells [8,26] and engineered human blood vessels in kidney organoids in vitro [27]. Among immune cells, SARS-CoV-2 appears to infect mononuclear phagocytes, but not lymphocytes [28,29].…”
Section: Sars-cov-2 Infection and Effects On Ifn And Statsmentioning
confidence: 99%
“…CQ/HCQ inhibits the activation of monocytes, macrophages [75], and T cells, and thereby reduces the release of pro-inflammatory cytokines (IL1B, IL6, TNF, IFNG, and others) [76]. However, a recent in vitro study performed in peripheral blood mononuclear cells has revealed that HCQ has minimal immunomodulatory activity [77]; but it must be noted that this study was performed under non-stimulatory conditions and might not mimic inflammatory conditions observed in SARS-CoV-2 infection or other autoimmune and inflammatory diseases.…”
Section: Coronaviridaementioning
confidence: 99%